Proteomic profiling of eIF3a conditional knockout mice - Zhuo, Wei; Chen, Juan; Jiang, Shilong; Zheng, Juyan; Huang, Hanxue; Xie, Pan; Li, Wei; Lei, Mengrong; Yin, Jiye; Gao, Ying; Liu, Zhaoqian (Frontiers in Molecular Biosciences, 2023)
Eukaryotic translation initiation factor 3 subunit A (eIF3a) is the largest subunit of the eukaryotic translation initiation factor 3 (eIF3). eIF3a plays an integral role in protein biosynthesis, hence impacting the onset, development, and treatment of tumors. The proteins regulated by eIF3a are still being explored in vivo. In this study, a Cre-loxP system was used to generate eIF3a conditional knockout mice. Tandem mass tag (TMT) labeling with LC-MS/MS analysis was used to identify differentially expressed proteins (DEPs) in fat, lungs, skin, and spleen tissue of the eIF3a knockout mice and controls. Bioinformatics analysis was then used to explore the functions and molecular signaling pathways of these protein landscapes. It was observed that eIF3a is essential for life sustenance. Abnormal tissue pathology was found in the lungs, fat, skin, spleen, and thymus. In total, 588, 210, 324, and 944 DEPs were quantified in the lungs, fat, skin, and spleen, respectively, of the eIF3a knockout mice as compared to the control. The quantified differentially expressed proteins were tissue-specific, except for eight proteins shared by the four tissues. A broad range of functions for eIF3a, including cellular signaling pathway, immune response, metabolism, defense response, phagocytes, and DNA replication, has been revealed using bioinformatics analysis. Herein, several pathways related to oxidative stress in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, including nitrogen metabolism, peroxisome, cytochrome P450 drug metabolism, pyruvate metabolism, PPAR signaling pathway, phospholipase D signaling pathway, B-cell receptor signaling pathway, ferroptosis, and focal adhesion, have been identified. Collectively, this study shows that eIF3a is an essential gene for sustaining life, and its downstream proteins are involved in diverse novel functions beyond mRNA translational regulation.